2006
DOI: 10.1093/ajcn/84.2.442
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of fatty acids in serum lipids as a measure of dietary fat quality in relation to the metabolic syndrome in men

Abstract: Background: A specific fatty acid (FA) composition in plasma lipid esters is related to the metabolic syndrome (MetS) and may influence the development of the MetS. Objective: The objective was to define and study FA factors as measures of dietary fat quality and endogenous FA metabolism in relation to MetS. Design: Principal factor analysis was performed to define specific FA factors in men participating in a population-based cohort studythe Uppsala Longitudinal Study of Adult Men. The factors were generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 34 publications
10
66
4
Order By: Relevance
“…Our results are comparable with the only other study to analyse data from fatty acid patterns derived from PCA (Warensjo et al, 2006), which also found an SFA pattern and an omega 3 pattern. As the negative relationship between individual saturated fats and metabolic and CVD risk, and the positive relationship with individual omega 3 fats (Keys, 1980;Hu et al, 2001;Kris-Etherton et al, 2001) is well known, it is important to elucidate whether overall patterns of free fatty acid status, characterized by either high Fatty acid patterns and CVD risk PML Skidmore et al saturated fat or high omega 3 content, would result in similar relationships to CVD risk.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are comparable with the only other study to analyse data from fatty acid patterns derived from PCA (Warensjo et al, 2006), which also found an SFA pattern and an omega 3 pattern. As the negative relationship between individual saturated fats and metabolic and CVD risk, and the positive relationship with individual omega 3 fats (Keys, 1980;Hu et al, 2001;Kris-Etherton et al, 2001) is well known, it is important to elucidate whether overall patterns of free fatty acid status, characterized by either high Fatty acid patterns and CVD risk PML Skidmore et al saturated fat or high omega 3 content, would result in similar relationships to CVD risk.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research in this area (Warensjo et al, 2005) indicates that these disturbances in fatty acid conversion are more often observed in those with metabolic syndrome when compared with those without it and that, in a longitudinal study, these disturbances predate the development of metabolic syndrome (Vessby, 2000;Warensjo et al, 2006). Another limitation is that it is not known whether factors including lifestyle and genetics are involved in the development of alterations in fatty acid desaturation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by our findings of a difference in hearing loss between the highest en lowest quartile of -0.8 dB in subjects of 50-60 yrs, and -1.5 dB in subjects of 60-70 yrs. Moreover, although the range of plasma very long-chain n-3 PUFA proportions in our study population was similar to that of other large studies in older adult populations (12,16), it could be possible that the differences in hearing loss between the quartiles become even more pronounced if this range would have been wider.…”
Section: N-3 Fatty Acids and Age-related Hearing Losssupporting
confidence: 79%
“…C17:0 results 7,10,22) . C15:0 and C17:0 are contained in various plant and animal foods but only in small amounts.…”
Section: Discussionmentioning
confidence: 99%